Pollution, Governance, and Women's Work: Examining African Female Labour Force Participation in the Face of Environmental Pollution and Governance Quality Puzzles - Kingsley Ikechukwu Okere; Stephen Kelechi Dimnwobi; Chukwunonso Ekesiobi; Favour Chidinma Onuoha (African Governance and Development Institute (AGDI), 2023)
In a rapidly changing world marked by environmental degradation and governance disparities, understanding their impact on African women's participation in the labor force remains a critical puzzle. This research seeks to unveil the intricate connections between pollution, governance quality, and women's economic engagement in Africa, shedding light on vital pathways to empower women, mitigate pollution's impact, and drive sustainable development in the region. Specifically, this study evaluates the impacts of governance quality and environmental pollution on gender economic outcomes in Sub-Saharan Africa (SSA) using data from 28 nations spanning 1996 to 2020. The study employs the dynamic panel threshold model. The key results reveal a negative and significant influence of ecological footprint on female economic participation. Furthermore, the dynamic threshold analysis reveals that environmental degradation undermines female labour engagement irrespective of the threshold level. The study also showed that below the threshold level, the interaction between governance quality variables and the ecological footprint exacerbates the negative impact of the ecological footprint on women's economic participation. Above the threshold level, the interaction between governance quality variables and the ecological footprint mitigates the negative impact. Overall, key recommendations like improved pollution control measures, inclusive governance, and effecting targeted policies and programs to empower women economically, among others, are proffered to contribute to the improvement in governance, environmental sustainability, and gender economic outcomes in SSA.
Keywords: 330; Governance quality; Environmental pollution; Gender economic outcomes; SubSaharan Africa